Strategies and Challenges in Translating Emotional Nuances: : Appraisal Theory in Inside Out 2 Subtitles - Effendi, Andita Putri (Language Horizon: Journal of Language Studies, 2025)
This study investigates the translation strategies employed to convey emotional nuances in the subtitles of the animated film Inside Out 2. The research adopts a qualitative content analysis approach to examine how translators handle the complex task of preserving emotional authenticity across languages. Using a purposively selected sample of subtitle segments, the study identifies predominant translation techniques by Molina & Albir theory of translation, such as adaptation, amplification, borrowing, calque, compensation, description, discursive creation, generalization, literal translation, linguistic amplification, modulation, particularization, reduction, substitution, variation, linguistic compression, establish equivalence and transposition. The findings reveal that the balance between linguistic accuracy and cultural relevance presents significant challenges for subtitle translators. The study emphasizes the significance of employing subtle translation techniques to retain the original dialogue's emotional effect. The results indicate that achieving emotional authenticity necessitates a careful balance between the cultures of the source and target languages, with literal translation emerging as the predominant approach. The research further demonstrates that both positive and negative emotions are conveyed through a variety of methods aimed at preserving psychological and cultural integrity. This work advances translation studies by shedding light on the complexities of translating emotions and offers valuable insights for translators and educators specializing in subtitling. Suggestions for future inquiry stress the need for deeper investigation into emotional subtitling across different film genres.